2022
DOI: 10.1002/jmv.27983
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay and mass cytometry revealed immunological profiles induced by inactivated BBIBP COVID‐19 vaccine

Abstract: With the global prevalence of COVID‐19 and the constant emergence of viral variants, boosters for COVID‐19 vaccines to enhance antibody titers in human bodies will become an inevitable trend. However, there is a lack of data on antibody levels and the protective effects of booster injections. This study monitored and analyzed the antibody potency and the antibody responses induced by the booster injection in the subjects who received three vaccine doses. The study was conducted in a multicenter collaboration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…However, the antibody responses after BV in PLWH remain unknown. In this study, the antibody seroprevalence and titers were increased after booster inactivated vaccination in PLWH, and a similar phenomenon was observed in previous studies on mRNA vaccines in healthy population 19–22 . In detail, a third mRNA vaccine dose boosted the neutralization titer to an average of fourfold higher than 1 month after two dose levels in PLWH, which was similar to our results (3.7‐fold) 22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the antibody responses after BV in PLWH remain unknown. In this study, the antibody seroprevalence and titers were increased after booster inactivated vaccination in PLWH, and a similar phenomenon was observed in previous studies on mRNA vaccines in healthy population 19–22 . In detail, a third mRNA vaccine dose boosted the neutralization titer to an average of fourfold higher than 1 month after two dose levels in PLWH, which was similar to our results (3.7‐fold) 22 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the antibody seroprevalence and titers were increased after booster inactivated vaccination in PLWH, and a similar phenomenon was observed in previous studies on mRNA vaccines in healthy population. [19][20][21][22] In detail, a third mRNA vaccine dose boosted the neutralization titer to an average of fourfold higher than 1 month after two dose levels in PLWH, which was similar to our results (3.7-fold). 22 However, a 27-fold higher antibody titer was observed 1 month after the third heterologous vaccine dose than that observed 6 months after two doses of ChAdOx1 nCoV-19 in PLWH, which was obviously higher than the results of this study (sixfold).…”
Section: Discussionsupporting
confidence: 91%
“…This theory is supported by our data demonstrating that the inactivated vaccination can promote humoral immunity, reflected in the marked decline in B-cell counts. The recent study also demonstrated a similar result in the substantially reduced humoral B-cell levels measured using the CYTOF method in humans after a month of immunizing with the inactivated vaccine [26]. The specific SAR-CoV 2 antibody level was maintained for at least 6 months after vaccination with the inactivated vaccine [27].…”
Section: Discussionmentioning
confidence: 68%
“…The titers of SARS‐CoV‐2 IgG and neutralizing antibodies increased to high levels at the first month after receiving the second dose and declined slowly thereafter. The significant peak of the antibody titer levels after injection of the booster dose highlights the recall immune response ( 20 ). A study on children aged 3-12 years received two doses of inactivated SARS-CoV-2 vaccines in Bahrain showed that vaccination led to a promising immunogenicity.…”
Section: Resultsmentioning
confidence: 99%